Is psychosexual therapy a reliable alternative to bupropion extended-release to promote the sexual function in infertile women? An RCT - Hajar Pasha; Zahra Basirat; Mahbobeh Faramarzi; Farzan Kheirkhah (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Various treatment methods are used to deal with sexual problems. Objective: This study was applied to answer the question of whether psychosexual therapy (PST) can be a reliable alternative to bupropion extended-release (BUP ER) to promote sexual function in infertile women. Materials and Methods: In this randomized clinical trial, 105 infertile women with sexual dysfunction were randomly allocated to three groups: PST, BUP ER, and a control group. The PST group participated in a total of eight 2-hr group sessions. In BUP ER group, 150 mg/day Bupropion ER was administered for eight weeks. The control group did not receive any interventions. The female sexual function index (FSFI) and a clinical interview were used to assess their sexual dysfunction. Results: The mean pre-to-post treatment scores of FSFI and its subscales increased significantly in PST and BUP ER groups (except in the subscale of sexual pain) (p = 0.0001, p = 0.0001). The changes in the subjects were not significant in the control group. After adjusting for the baseline values, the results remained significant for the mean FSFI (p = 0.0001), and its subscales between the groups. Compared to the control group, a significant increase was observed in the mean FSFI (p = 0.0001, p = 0.002) and its subscales in the PST group and in the BUP ER group (except in the subscale of sexual pain). Comparison of two intervention methods showed that PST had the better effect on the sexual function improving (p = 0.0001) and its subscales (exempting the subscale of orgasm) than BUP ER. Conclusion: PST can be considered not only a reliable alternative to pharmacotherapy; it also produces better results in terms of improving sexual function in infertile women.